Pengaruh Sistem Pengendalian Intern dan Sistem Akuntansi Keuangan Daerah Terhadap Kualitas Laporan Keuangan Pemerintah di Pemerintahan Kabupaten Malang - Fahkrurrohim Hardika Wibisono; Junaidi Junaidi; Hariri Hariri (Universitas Islam Malang, 2023)
This research aims to analyze the effect of internal control and regional financial accounting systems on the quality of financial reports in the Malang Regency Government. The population used in conducting this research was 40 people who work in accounting. The data collection technique in this study was purposive sampling. The sample selected was 36 people with data collected using the questionnaire method. The test used in this research is simultaneous or joint testing (t), the test of the coefficient of determination (R2), and partial testing (f). The results showed that the t-test in the independent variable had a significant effect on the dependent variable. Meanwhile, in the f-test two variables influence the quality of financial reports in the Malang Regency Government.Keywords: Internal control system, regional financial accounting system, quality of financial statements, government of Malang regency.